Stability-indicating HPLC-DAD method for the simultaneous determination of fluoroquinolone in combination with a non-steroidal anti-inflammatory drug in pharmaceutical formulation - Elaine de Oliveira Araujo; Aline Marques Rosa; Marcos Serrou do Amaral; Rúbia Adrieli Sversut; Adriano César de Morais Baroni; Lincoln Carlos Silva de Oliveira; Nájla Mohamad Kassab (Universidade de São Paulo, 2020)
We developed and validated a stability-indicating assay method for the simultaneous determination of enrofloxacin and piroxicam in combination and in the presence of degradation products. Reverse-phase high-performance liquid chromatography analyses were carried out on a Vertisep C18 column and acetonitrile-water (48:52 v/v, pH 3.0) mobile phase with a 1.00 mL min−1 flow rate. The efficient chromatographic separation of these drugs and their forced degradation products was achieved in less than 5min with a peak purity match factor higher than 950. The method used showed linearity in the concentration ranges of 0.25 to 16.0 µg mL−1 for enrofloxacin (r = 0.9997) and 0.125 to 8.0 µg mL−1 for piroxicam (r = 0.9999) as well as precision (relative standard deviation lower than 2%), accuracy (mean recovery 100 ± 2%), and robustness, according to ICH (International Conference on Harmonization) and AOAC (Association of Official Analytical Chemists) guidelines. This method can simultaneously determine the combination of these drugs in a veterinary formulation and separate the drug peaks from their forced degradation products. Additionally, its optimized chromatographic conditions can contribute to the quality control of this formulation in pharmaceutical manufacturing plants and minimize waste from the organic solvent.